Probabilistic characteristics of narrow-band processes at phase measurements - Куц, Ю.В.; Щербак, Л.М. (Proceedings of National Aviation University (archive), 2004)
The probabilistic model of narrow-band process phase characteristics is offered and investigated. The geometrical interpretation of model is given. The model describes a wide class of signals, and the results of its research can find application at statistical processing of phase measurements results.